17-DMAG induces Hsp70 and protects the auditory hair cells from kanamycin ototoxicity in vitro. (19th February 2015) - Liu, Yun; Yu, Yang; Chu, Hanqi; Bing, Dan; Wang, Shaoli; Zhou, Liangqiang; Chen, Jin; Chen, Qingguo; Pan, Chunchen; Sun, Yanbo; Cui, Yonghua
Highlights: 17-DMAG induces Hsp70 over-expression in the cultured organ of Corti. 17-DMAG attenuates the ototoxity of kanamycin to hair cell in the organ of Corti. 17-DMAG might become an effective therapeutic drug for auditory hair cells. Abstract: Heat shock protein 70 (Hsp70) has been known to be able to play a protective role in the cochlea. The aim of this study was to investigate whether geldanamycin hydrosoluble derivative 17-(dimethylaminoethylamino)-17-demethoxygeldanamycin (17-DMAG) has the ability to induce Hsp70 up-regulation to protect hair cells from kanamycin-induced ototoxicity in vitro . The organ of Corti (OC) explants were isolated from mice at postnatal day 3–5. Then, the explants were exposed to kanamycin with or without pre-incubation with 17-DMAG. The expression of Hsp70 was assessed by reverse transcription-quantitative polymerase chain reaction, ELISA, and immunofluorescent staining. The surviving hair cells were examined by phalloidin labeling and were counted. We found that Hsp70 expression in the explants after pre-incubation with 17-DMAG was significantly increased at both mRNA and protein levels. Immunofluorescent staining showed that Hsp70 was mainly located in the auditory hair cells. Compared with kanamycin group, the loss of hair cells was inhibited significantly in 17-DMAG + kanamycin group. Our study demonstrated that 17-DMAG induces Hsp70 in the hair cells, and has a significant protective effect against kanamycin ototoxicity in vitro . 17-DMAG has the possibility to be a safe and effective anti-ototoxic drug.